What still presents urgently to ENT during a pandemic? Experience of an ENT rapid access clinic during the coronavirus disease 2019 pandemic. Issue 1 (7th January 2021) - Stubington, T J; Morrison, B; Sevilla, C; Judd, O
Abstract: Objectives: This study sought to determine the conditions that still present to ENT despite government advice to avoid unnecessary travel. It also assessed the impact of social distancing on pathologies presenting to ENT and reviewed the usefulness of telephone consultations in semi-urgent presentations. Method: A retrospective review was conducted of 97 instances of patient care carried out in the rapid access ENT clinic at a large district general hospital. Results: Otitis externa and foreign bodies represented 25 per cent and 13 per cent of consultations respectively. Tonsillitis and peritonsillar abscess were uncommon, representing 6 per cent of total consultations. Telephone appointments represented only 28 per cent of total consultations; however, they appeared to reduce the number of physical appointments required. Conclusion: Otitis externa and foreign bodies continue to be common during the pandemic. Social distancing measures reduced the number of tonsillitis and quinsy presentations. Telephone consultations are effective for certain urgent presentations to ENT, most noticeably nasal trauma and follow up of non-serious pathologies.